Pedestrian safety and security for female users in urban alleys: a systematic review - Xu, Tengyun; Abdul Aziz, Faziawati; Ujang, Norsidah; Hasna, Mohd Fabian; Mundher, Riyadh; Shahidan, Mohd Fairuz; Zhao, Jing (Jomard Publishing, 2024)
The world's rapid urbanization has led to the emergence of hundreds of alleys between towering skyscrapers. Nowadays, there is numerous safety issues associated with urban alleys and people often associate these alleys with dirt, crime and fear. Consequently, using urban alleys hinders people-especially women-from obtaining basic essentials for safety. Numerous studies have indicated that women perceive cities differently than males and they typically feel more uneasy in public places. The purpose of this article is to investigate strategies and features that can enhance the safety of female pedestrians in urban alleys. After thoroughly examining the Web of Science and Scopus databases, 45 publications were identified. These articles were selected by incorporating keywords such as urban alleys, safety, female users and relevant keywords. The review encompasses information on data collection methods, sample strategies, data analysis and outcome analysis. The study reveals that physical factors, social, psychological and crime prevention factors also influence how women use urban alleys. Nevertheless, women's perceptions of the safety of urban alleys are significantly influenced by physical factors. Ultimately, these findings provide managers, planners and urban designers with valuable insights to establish a foundation for safer urban settings.